2010
DOI: 10.1159/000314657
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Acute Puumala Hantavirus Infection Does Not Predict the Long-Term Outcome of Patients

Abstract: Background/Aims: We have found greater urinary protein excretion and higher glomerular filtration rate (GFR) and blood pressure in patients 6 years after acute nephropathia epidemica (NE) compared with seronegative controls. The present aim was to establish whether the long-term outcome is determined by the severity of acute illness. Methods: Serial plasma interleukin-6 (IL-6), tumour necrosis factor-α (TNF-α), creatinine, C-reactive protein, blood cell count as well as 24-hour urinary protein and overnight α<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, although the general prognosis of PUUV infection is positive, the development of a chronic hormonal deficit following PUUV infection with pituitary involvement remains a possibility [41]. The long-term outcome, with reference to renal function, blood pressure, urinary protein excretion or the occurrence of hormonal defects, cannot be predicted by the clinical severity of acute PUUV infection [33,41]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, although the general prognosis of PUUV infection is positive, the development of a chronic hormonal deficit following PUUV infection with pituitary involvement remains a possibility [41]. The long-term outcome, with reference to renal function, blood pressure, urinary protein excretion or the occurrence of hormonal defects, cannot be predicted by the clinical severity of acute PUUV infection [33,41]. …”
Section: Discussionmentioning
confidence: 99%
“…The study cohort consisted of 556 PUUV-infected patients, who had participated in our previous clinical studies [12,17,18,19,24,25,26,27,28,29,30,31,32,33,34,37,38,39,40,41]. The diagnosis of acute PUUV infection was serologically confirmed in all cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human PUUV infection causes a mild form of HFRS, and the majority of patients recover without any long‐term consequences . However, transient symptoms related with central nervous system (CNS) involvement are common and cases of pituitary haemorrhage followed by hypopituitarism have been described .…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up 10 years after PUUVinfection revealed no clear long-term consequences [68], suggesting that hantaviruses normally do not cause long-term consequences. Furthermore, it was recently shown that there is no correlation between severity of acute PUUV-caused HFRS and long-term outcome of patients [69], suggesting that, if there are long-term consequences of hantavirus infection, hitherto unknown factors determine the long-term outcome. In contrast to what is observed in natural hosts [9,70], viremia during HFRS/HCPS is believed to be transient.…”
Section: Long-term Consequences Of Hantavirus Infectionmentioning
confidence: 99%